Privacy preserving transactions on public blockchain - Andriani, Fransisca (Nanyang Technological University, 2019)
The abundance of data available on public blockchain environments might expose users to privacy breaching. Ethereum as the largest host of blockchain-based project currently has no robust protection against such threats. In this paper, a proof-of-concept decentralized application is implemented demonstrating privacy preserving transaction flow in Ethereum environment using zero-knowledge cryptography (zk-SNARK ). The design of the application utilized an experimental package, EY Nightfall and focuses on a blind auction scenario where personal informations needs to be protected. The proof-of-concept is then analysed to weigh the financial and temporal costs of the implementations against the security advantages and was found to be feasible for non fast-paced settings and significantly large transactions.